Interrater Agreement of Manual Palpation for Identification of Myofascial Trigger Points: A Systematic Review and Meta-Analysis. Issue 8 (August 2017) - Rathbone, Alasdair T.L.; Grosman-Rimon, Liza; Kumbhare, Dinesh A.
Abstract : Objective: To achieve a statistical estimate of the agreement of manual palpation for identification of myofascial trigger points (MTrPs) and secondarily to investigate potential factors impacting the agreement of this technique. Methods: We searched MEDLINE(R) and Embase for studies examining the reproducibility of manual palpation for the identification of MTrPs from the year 2007 to present. In addition, we utilized studies identified by 2 comprehensive systematic reviews that covered the period before 2007. The included studies were original peer-reviewed research articles and included Cohen κ measures or data with which to calculate Cohen κ. Studies were excluded if they lacked a measure of variability or information required to calculate variability. Studies that examined palpation through body cavities were also excluded. Of the 18 potentially relevant articles only 6 met inclusion criteria including 363 patients. Modified QUADAS tool was used to assess study validity. Subgroup comparisons were made utilizing Q and Z tests. Results: An estimate of κ=0.452 (95% confidence interval, 0.364-0.540) was obtained for interrater agreement of manual palpation of MTrPs. Localized tenderness (κ=0.676) and pain recognition (κ=0.575) were the most reliable criteria. Only 1 study met inclusion criteria for intrarater agreement and therefore no meta-analysis was performed. Discussion: Use of manual palpation for identification of MTrPs is unreliable, and future investigation should focus on integration with more reliable techniques.